Chest Pain in Young Patients (5-15 Years) Referred to Pediatric Cardiology Outpatient Clinic - Masroor Hussain Sharfi, Anum Abbas, Riffat Farrukh, Muhammad Uzair, Shaheen Masood, Abdulhadi Abdullah Alghamdi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chest pain is the communal complaint among pediatric age groups. Chest pain due to heart disease is rare in children and adolescents, with an incidence of less than 6%. History and physical examination may be sufficient to identify the most important etiologies. Aim: The aim of the study is to review various causes of chest pain in young patients admitted to a pediatric cardiology clinic. Method: We retrospectively analyzed the clinical data of our patients visited to emergency or outpatient clinics in our hospital with chest pain from March 2022 to October 2022. A total of 56 patients (36 females and 20 males), aged 5-15 years were included in this study. Follow-up of the patients was carried out by calling all relatives of the patient and asking about the child’s condition and chest pain. Clinical history and physical examination were performed. Results: A total of 56 patients between the ages of 5 and 15 were enrolled in the study, with a mean age of 11.78 ± 2.95 years. Six cases (10.7%) were identified to have a cardiac cause. 16 individuals (28.6%) had a respiratory cause identified. 3(5.4%) of patients referred to a gastroenterology clinic with gastrointestinal causes. The diagnosis of idiopathic chest pain was made in 6 individuals (10.7%) after a negative history, physical examination, and testing. Conclusion: Chest pain in children is usually mild. However, thorough physical examination and detailed history should be performed to detect any signs of disease. Keywords: Chest pain, Pediatric patients, Echocardiography.